(untitled) (Fiep Bulletin - online, 2014)
Currently in a gradual process reflects the body of the man; lived, suffered body, kept out of society, exploit, mechanized, at last, the-subjected to a directed capitalist system to the consumption and the profit. The body is the way for which the life enjoys, body this that suffers transformations since the ancient times, however without many analyses on such phenomenon, being thus necessary that this body is thought, reflected and understood, because knowing and reflecting on the description and the mutations of what if it searchs it will only be possible to get knowledge so that it has an attempt of agreement of the many attitudes taken for the man in the currently. For the professionals whom the body has as work object, if it makes important to discover it, feel it and knows it. The present work has as objective to verify which the social representation of the body for the teachers of the courses of graduation in Physical Education of the Institutions of the West of the Paraná. The characterization of this research if gives of qualitative form and etnográfica, searching to analyze in it speaks of the teachers; vocational training of professional futures, its representation on body and as the same one happens in the shape to teach. Having this study as sampling 18 chosen teachers, 3 of each institution. An interview half-structuralized with not fixed script was used as instrument, and for the analysis and interpretation of the information it opted itself to the category, way that it propitiated to find in the speech of the teaching words or phrases that had identified its thought. Of unanimous form, we identify in the silence of the speeches a cartesian look of the study object, this is double in body and soul, when the spalling is not deeper, a functional detailing of the organic one, cells and systems. The shape to teach of these vocational training cannot neglect the same ones, thus reflecting on the formation of the learning, but for being a representation it can suffer mutation, is enough quality in the reconstruction.